Alvarado Score: still relevant in diagnosis of acute appendicitis: a prospective study with histopathological correlation - Jain, Rushil; Jain, Vimal; Jolly, Shalit (International Surgery Journal, 2017)
Background: Acute appendicitis is the most common abdominal emergency. Although abdominal surgeons have been encountering the acute appendicitis for more than 100 years, prompt diagnosis is still elusive in order to reduce morbidity and to avoid serious complications. Present study was conducted to evaluate the usefulness of Alvarado score in diagnosing acute appendicitis and its role in minimizing the negative appendectomy rate and correlating the same with histopathological findings of appendectomy specimens. Methods: This prospective correlational study was conducted in the Department of General Surgery, Mata Chanan Devi Hospital, New Delhi for a period of one year from January 2014 to December2014.Complete clinical history of the patients was collected in a predesigned proforma. A complete physical and systemic examination was done for all patients. Based on the Alvarado scoring system the patients were divided into three categories. Category 1 (score ranging from 1-4), Category 2 (score ranging from 5-6), Category 3 (score ranging from 7-10). Specimen of removed appendix was sent for histopathological examination and clinically correlated those findings with Alvarado score. Sensitivity, specificity, positive negative likelihood ratios, positive and negative predictive values and negative appendectomy rate were calculated. Results: Out of 100 cases (56 males and 44 females) 15 belonged to category-I, 30 belonged to category-II and 55 belonged to category-III. Surgical procedures were done in 67 patients along with conservative management. Final diagnosis by histopathology was found in 58 cases. The sensitivity and specificity of Alvarado score was found to be 89.66% and 92.86% respectively. PPV and NPV of Alvarado score is 94.55% and 86.67% respectively. The negative appendectomy rate was 13.4%. Conclusions: Alvarado score is a simple non-invasive diagnostic procedure, which is reliable, safe, repeatable and economical, easy and can be used in emergency setting, without expensive and complicated supportive diagnostic tool in diagnosing acute appendicitis and thus still very much relevant in today’s modern era with availability of gamut of expensive imaging techniques.